Corrosion Behavior of API X100 Steel Material in a Hydrogen Sulfide Environment - Paul Okonkwo (831577) (2017)
Corrosion Behavior of API X100 Steel Material in a Hydrogen Sulfide Environment Other Information Published in: Metals License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/met7040109